BIBLIOMETRIC ANALYSIS OF GLOBAL MARITIME AND ECONOMIC LITERATURE (2010–2023) USING THE VOSVIEWER APPROACH - Saepulloh, Asep; Alam, Al Fajar; E.Y., M. Habib (Jurnal Segara, 2025)
The maritime sector plays a pivotal role in supporting economic growth, serving both as a critical source of employment and a driver of national development. This study is motivated by the lack of comprehensive, systematic mapping of the global scholarly landscape on maritime economics. The research aims to identify prevailing trends, key contributors, and dominant themes in maritime economic literature published between 2010 and 2023. A bibliometric analysis was conducted using data retrieved from the Scopus database, filtered by the keywords “maritime” and “economy.” A total of 2,712 documents were analyzed using VOSviewer to construct and visualize co-occurrence networks of keywords, authorship patterns, institutional affiliations, and country-level collaborations. The results indicate an average annual publication growth rate of 19%, with Marine Policy identified as the most prolific journal and Dalian Maritime University as the leading institution in terms of scholarly output. Core research themes include “maritime transportation” and “ship” operations, while environmentally critical topics such as marine pollution and sustainability remain underrepresented. The findings highlight the need for broader interdisciplinary exploration, particularly in integrating environmental concerns within maritime economic discourse. This study provides a robust foundation for guiding future research agendas and policy development in advancing a more sustainable and inclusive maritime economy.